Assessing Carnivore Occurrence and Community Attitudes Towards Wildlife in a Multi-Use Arid Landscape Corridor - Kannan, Prameek; Salaria, Saloni; Khan, Siddique; Mark, Tanuj; Baberwal, Navin; Bhatnagar, Abhishek; Shethia, Yash; Thatte, Prachi; Chanchani, Pranav (Frontiers in Conservation Science, 2022)
Small population sizes, low densities, and large area requirements make large carnivores particularly sensitive to habitat degradation and land-use change. In fragmented landscapes, many protected areas cannot accommodate viable wildlife populations in themselves, which brings the surrounding human-dominated matrix that may extend wildlife habitats or serve as corridors into focus. Such areas are typically excluded from the conservation portfolio and are subject to rapid land -use change in many areas. This study investigates the occurrence of tigers, sloth bears, leopards and striped hyenas and assesses community use of natural resources and attitudes towards wildlife in a 3384 km2 portion of semi-arid multiple-use landscape in Western India that also serves as an important wildlife corridor. This area abuts Ranthambore Tiger Reserve, a preeminent protected area in Western India. Sign surveys spanning 1039.22 km of trails were conducted in 94, 36 km2 grids spanning agricultural land, forests and other land use types to collate information on wildlife occurrence and associated environmental and human factors. Analysis using occupancy models revealed that tiger and sloth bear occurrence probabilities, (0.093 ± 0.05) and (0.13 ±0.02) were considerably lower than those for leopards (0.72 ±0.22) and striped hyenas (0.91 ±0.08). Lack of sufficient cover and limited food availability renders these multiple-use habitats poorly suited for tigers and sloth bears, while leopards and hyenas are able to adapt better to multi-use areas. Concurrently, 66 villages were surveyed across the study landscape, where data on broad socio-economic attributes of communities and their attitudes towards wildlife were assessed through questionnaire surveys. More respondents expressed negative attitudes than positive attitudes which vary as a function of education levels, occupation and land holding sizes. Ongoing landscape transformation through mining, agricultural expansion, infrastructure development, and negative attitudes towards wildlife conservation among people living in the agricultural matrix threatens the long-term functionality of these corridors. Therefore immediate measures are needed to develop and implement corridor conservation strategies and plans, with a focus on land use planning and human-wildlife conflict mitigation. In the absence of decisive and timely action, wildlife populations may increasingly get relegated to fragmented patches, jeopardising their persistence.